Legal Protection for ChatGPT (Generative Preb-Trained Transformer) Users as A Form of Health Services Innovation from The Perspective of Law Number 17/2023 on Health - Khamozaro Waruwu; Afiif Hadiani Pratiwi (Universitas Muhammadiyah Surakarta, 2024)
Today's technological advancement has given birth to the artificial intelligence technology (AI), of which one of its examples is ChatGPT. ChatGPT is a type of artificial intelligence which can duplicate human intelligence and behave like a human being in order to solve certain task or assignment. In this paper, we apply normative juridical analysis method through in-depth study and analysis of legal issues through literature study of relevant regulations, as they are currently enforced in Indonesia. In the field of health services, the utilisation of ChatGPT is done to provide automated medical record brief from interaction with patients so as to create efficiency in medical documentation. Another consequence that arises from the use of ChatGPT artificial intelligence is its implementation towards ethical and legal issues, where legal protection for its users shall be further studied in order to create a sense of balance in its utilisation. This analysis deduces that current Indonesian legal regulation has not comprehensively and specifically regulated artificial intelligence as well as ChatGPT. Therefore, a specific regulation on artificial intelligence is necessary to protect national, social, and private interests from misuse of, and negative impacts of, artificial intelligence to ensure legal certainty.